Analisis penyebab kesalahan penggunaan kalimat efektif dalam teks narasi peserta didik kelas v sekolah dasar - Pratiwiningrum, Yunita; Rukayah, Rukayah; Ardiansyah, Roy (Universitas Sebelas Maret, 2022)
This study aims to describe the causes of errors in the use of effective sentences in narrative texts of fifth grade students at SD Negeri Kadokan 01 Sukoharjo. This research is a descriptive qualitative research with case study approach. The research data is qualitative data. The data sources for this research were informants (5 students of class V SD Negeri Kadokan 01 Sukoharjo) and documents (narrative texts of students of class V SD Negeri Kadokan 01 Sukoharjo). The subject selection technique was carried out by using purposive sampling technique. Data collection techniques were carried out through document analysis, in-depth interviews, and questionnaires. Data validity testing techniques were carried out by technical triangulation and member checks. Data analysis techniques were performed using interactive data analysis techniques by Miles, Huberman, and Saldana. The results of this study are as follows. The causes of errors in the use of effective sentences of students consist of factors that cause the ineffectiveness of sentences and factors that cause errors in the use of effective sentences. The causes of errors in the use of effective sentences found in narrative texts of fifth grade students at SD Negeri Kadokan 01 Sukoharjo different from one student to another.Kata kunci: causes of mistakes, effective sentences, narrative text